THE IMPLEMENTATION OF FUZZY-TSUKAMOTO METHOD IN MAKING THE BEST DECISION TO BUY A SMARTPHONE - Adwitya Rai Paramaartha; Rikip Ginanjar (IT for Society, 2020)
Smartphone is one of the most important things for people nowadays. The increasing number of products as well as the amount information carried by each brand of smartphone can overload, there are many things to consider before buying a smartphone. Fuzzy logic is a form of many- valued logic in which the truth values of variables may be any real number between 0 and 1. Fuzzy logic is one method to analyze system containing uncertainty. This study aims to use fuzzy logic in helping people make decisions on buying the most suitable smartphone for them by producing an output value that can help the user to determine which smartphone will be purchased based on user’s ideal criteria of a smartphone.